Critical Success Factors Analysis On International Financial Reporting Standard Implementation In Indonesia - Arie Pratama (Universitas Pendidikan Indonesia, 2023)
In 2009 â€“ 2012, Indonesia adopt International Financial Reporting Standard (IFRS) into its accounting standard. Indonesia accounting standard board believe that IFRS adoption will increased quality of accounting information.Â The convergence process face several difficulties and constraint due to several problem regarding human resource, infrastructure, and regulation. This research purpose is to describe three critical sucess factors for in Indonesia. Three critical success factors are: Human Resources Education, Business Process Infrastructure, and Regulation harmonization. Research done using qualitative descriptive method with case study approach. To assess the impact level of three critical sucess factors, researcher compare Indonesia condition with other countries adopted IFRS. The research show that all three factors affect Indonesia and other countries implemented IFRS. Researcher suggest several action to be done, so the convergence process can be done effectively.